2010
DOI: 10.3758/s13414-010-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of decision making criteria: reward rate ultimately beats accuracy

Abstract: Speed-accuracy tradeoffs strongly influence the rate of reward that can be earned in many decision-making tasks. Previous reports suggest that human participants often adopt suboptimal speed-accuracy tradeoffs in single session, two-alternative forced-choice tasks. We investigated whether humans acquired optimal speed-accuracy tradeoffs when extensively trained with multiple signal qualities. When performance was characterized in terms of decision time and accuracy, our participants eventually performed nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
255
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(269 citation statements)
references
References 27 publications
12
255
2
Order By: Relevance
“…These results suggest that becoming more cautious when evidence becomes more ambiguous is a powerful heuristic, one that is intuitive and probably reinforced by everyday experience. Indeed, Balci et al (2011) found that even young participants with 13-15 sessions of practice on a decision task were too cautious to optimize reward rate in the difficult condition, despite performing close to reward-rate optimal in easier conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results suggest that becoming more cautious when evidence becomes more ambiguous is a powerful heuristic, one that is intuitive and probably reinforced by everyday experience. Indeed, Balci et al (2011) found that even young participants with 13-15 sessions of practice on a decision task were too cautious to optimize reward rate in the difficult condition, despite performing close to reward-rate optimal in easier conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, even the young participants showed limitations in their ability to optimize reward rate across the difficulty conditions with fixed-time blocks, and it is reasonable to think that these limitations would be more severe for the older population. Older participants might be less likely to explore different boundary settings or less able to monitor the accuracy and duration of their responses (Balci et al, 2011;Starns & Ratcliff, 2010). The deficit might also have a physiological basis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations